Medium-density fibreboard (MDF) from oil-palm fronds - Norhafzan, Junadi (2012)
Malaysia is one of the top five exporters of Medium-density Fibreboard (MDF) in the world in which total production capacity exceeds one million cubic metres per year. Most of MDF producers use rubberwood as their main raw material for manufactured products. Resulted from this, there was insufficient supply due to high demand particularly from the panel composite sector. The unsecure supply and price hike of rubberwood has led MDF industries to look for alternative raw material. Oil palm fronds (OPF) are readily available residues from palm oil industry and have tremendous potential to be used as fibre raw material in Malaysia. In this study, the manufacturing of MDF from oil palm fronds (OPF) was studied and characterized in order to measure the compatibility with MDF using rubberwood sources. The results proved that MDF produced from 100% OPF and its mixture offer good physical and mechanical properties. Although it gives high value for thickness swelling, the value is still acceptable with the commercialize standard. MDF from OPF also has sound absorption qualities that were generally superior at several frequencies compared to commercialize fibreboards samples. In other aspect of economic feasibility analysis, it was observed that MDF from oil palm fronds offering strategically lower price than other competitors product since it using low cost raw material. It also can gain niche in the market area due to the affordable price and will be able to generate highly predictable cash flows on a monthly basis from the manufacturing and distribution of the products. In conclusion, oil palm fronds can be a suitable alternative raw material in replacing the rubberwood sources for MDF production and very feasible to be manufactured in Malaysia